2018
DOI: 10.1590/abd1806-4841.20187309
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of the hospitalizations at a dermatologic ward (2007-2017)

Abstract: There is little data in the literature concerning dermatologic admissions. Several diseases are seasonal in incidence and clinical worsening. We performed a survey of hospitalizations in the dermatology ward of a public hospital (April/2007 to May/2017). There were 1790 hospitalizations, whose main diagnoses were infectious dermatoses, neoplasias, psoriasis, bullous diseases and cutaneous ulcers. In winter, there were fewer hospitalizations for bacterial infections and urticaria, but more for leprosy. In summe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
2
13
0
1
Order By: Relevance
“…A seasonal pattern has been proposed in a variety of skin disorders, including alopecia areata, psoriasis, acne, and atopic dermatitis. [5][6][7][8][9][10][11][12] Our findings revealed the lowest prevalence of SD during the summer in all age groups and for both sexes. This seasonal pattern may be related to increased ultraviolet radiation (UVR) exposure, higher levels of air humidity, and changes to the skin microbiome during warmer months.…”
Section: Discussionsupporting
confidence: 43%
“…A seasonal pattern has been proposed in a variety of skin disorders, including alopecia areata, psoriasis, acne, and atopic dermatitis. [5][6][7][8][9][10][11][12] Our findings revealed the lowest prevalence of SD during the summer in all age groups and for both sexes. This seasonal pattern may be related to increased ultraviolet radiation (UVR) exposure, higher levels of air humidity, and changes to the skin microbiome during warmer months.…”
Section: Discussionsupporting
confidence: 43%
“…A study on dermatological hospitalizations analyzed the profiles of admissions associated with the seasons of the year and showed that there was a higher incidence of leprosy. 37 A study that evaluated the presence of M. leprae in the nasal mucosa of the population identified seasonal variation and a possible association among environmental conditions (climate), the transmission patterns and levels of exposure to M. leprae. 38 In order to assure success in leprosy elimination program actions, it is necessary to understand the geographical distribution of the disease, its natural history and pathogen-host interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation was that the sample comprised only one epidemiologic week, which might have influenced the frequency of diseases with seasonal characteristics, such as psoriasis, leishmaniasis, and mycoses. 50 Nevertheless, the same epidemiological week was chosen as in the 2006 study to allow comparisons to be made, constituting the main source of information on the demand for dermatological services in Latin America.…”
Section: Discussionmentioning
confidence: 99%